Measuring farmers’ self-efficacy for managing perennial summer forages - Drysdale D; Hartnett MK; Sewell A; Gray D; Kemp P; Wood B (Austraasia Pacific extension network)
Farmers’ self-efficacy beliefs impact on their learning and decision-making processes, and as such provide vital information to agricultural extension providers. Self-efficacy is measured as an individual’s perception of what they ‘can do’, rather than what they ‘actually do’, providing an indication of their present efficacy to carry out a specific future task. This paper reports on the design, development and pilot study of a tool to provide quantitative measures of farmers’ self-efficacy when considering the introduction or management for perennial summer forages. Preliminary results indicate that this tool provides a robust means of measuring changes in self-efficacy beliefs within this specific domain of managing perennial summer forages. Understanding farmers’ efficacy beliefs may guide the design of more effective agricultural extension activities to better assist farmers in their learning and decision-making when adopting innovative agricultural practices.
Keywords: measuring self-efficacy; farmer learning; practice change